Three-dimensional potential energy surface of selected carbohydrates' CH/π dispersion interactions calculated by high-level quantum mechanical methods - Kozmon, Stanislav; Matuška, Radek; Spiwok, Vojtěch; Koča, Jaroslav (Chemistry (Weinheim an der Bergstrasse, Germany), 2011)
In this study we present the first systematic computational three-dimensional scan of carbohydrate hydrophobic patches for the ability to interact through CH/π dispersion interactions. The carbohydrates β-d-glucopyranose, β-d-mannopyranose and α-l-fucopyranose were studied in a complex with a benzene molecule, which served as a model of the CH/π interaction in carbohydrate/protein complexes. The 3D relaxed scans were performed at the SCC-DFTB-D level with 3 757 grid points for both carbohydrate hydrophobic sides. The interaction energy of all grid points was recalculated at the DFT-D BP/def2-TZVPP level. The results obtained clearly show highly delimited and separated areas around each CH group, with an interaction energy up to -5.40 kcal mol(-1) . The results also show that with increasing H⋅⋅⋅π distance these delimited areas merge and form one larger region, which covers all hydrogen atoms on that specific carbohydrate side. Simultaneously, the interaction becomes weaker with an energy of -2.5 kcal mol(-1) . All local energy minima were optimized at the DFT-D BP/def2-TZVPP level and the interaction energies of these complexes were refined by use of the high-level ab initio computation at the CCSD(T)/CBS level. Results obtained from the optimization suggest that the CH group hydrogen atoms are not equivalent and the interaction energy at the CCSD(T)/CBS level range from -3.54 to -5.40 kcal mol(-1) . These results also reveal that the optimal H⋅⋅⋅π distance for the CH/π dispersion interaction is approximately (2.310±0.030) Å, and the angle defined as carbon-hydrogen-benzene geometrical centre is (180±30)°. These results reveal that whereas the dispersion interactions with the lowest interaction energies are quite strictly located in space, the slightly higher interaction energy regions adopt a much larger space.
Keywords: nukleární magnetická rezonance biomolekulární; molekulární konformace; Thermodynamics; termodynamika; Molecular Conformation; sacharidy; kvantová teorie; stereoizomerie; Carbohydrates; Quantum Theory; chemické modely; Models, Chemical; Stereoisomerism; Nuclear Magnetic Resonance, Biomolecular